IL-6 is a prognostic biomarker in patients with advanced esophageal squamous cell carcinoma received with PD-1 inhibitors - Huang, Ping; Zhao, Manyi; Xia, Jianhong; Li, Hongliang; Sun, Junxia; Li, Xin; Yang, Chunsheng; Gao, Guangyi; Zhou, Wenhang; Zhong, Meifeng; Yong, Hongmei (Frontiers in Immunology, 2025)
BackgroundDue to the low efficacy rates, effective biomarkers are desperately needed to determine populations of advanced esophageal squamous cell carcinoma (ESCC) that may benefit from immune checkpoint inhibitor (ICI) treatment.ObjectivesTo explore the relationship between IL-6 and the esophageal cancer tumor immune microenvironment using online databases and esophageal cancer tissue microarrays and to investigate the predictive role of IL-6 for immunotherapy in esophageal squamous carcinoma patients through clinical study data.MethodsRNA-seq datasets of ESCC patients were obtained from TCGA, and the relationship between IL-6 and immune cells was discovered using TIMER 2.0 databases. CD8, IL-6, and PD-L1 expression in ESCC tissue microarrays were measured using immunohistochemistry, and then the tumor microenvironment was classified. Furthermore, blood specimens were collected from advanced ESCC patients before they received PD-1 inhibitors, and follow-up was conducted to gather clinical survival data. Based on IL-6 levels. We divided the population into the high and low IL-6 groups, comparing the efficacy and survival of the two groups.ResultsIL-6 positively correlated with mRNA levels of PD-L1, negatively correlated with immune cells, and positively correlated with immunosuppressive cells. High IL-6 expression in tissues might make PD-1/L1 blockade therapy less effective. Individuals with higher baseline plasma IL-6 levels had significantly lower objective remission rates and inferior PFS and OS. Elevated baseline IL-6 was demonstrated to be an independent risk factor for the prognosis of advanced ESCC patients using PD-1 inhibitors, according to COX regression analysis.ConclusionIL-6 overexpression correlates with the immunosuppressive tumor microenvironment in ESCC, and it can be a predictive biomarker in ESCC patients received with PD-1 inhibitors.